The Metaphysics of Reality and Objective Truth: Sa‘D Al-Dīn Al-Taftāzānī on Nafs Al-Amr - Saful Amin, Mohd Saiful Aqil Naim (Al-Basirah Journal, 2025)
This paper examines the epistemological framework of the influential Ash’arite theologian Saʿd al-Dīn al-Taftāzānī (d.792 H), focusing on his theory of nafs al-amr (the thing as it is) as a foundation for objective truth. It analyzes al-Taftāzānī’s critique of preceding models, particularly that of Naṣīr al-Dīn al-Ṭūsī and elucidates his argument that truth is a correspondence between a judgment and a mind-independent reality. The study demonstrates how this framework effectively counters sceptical and nihilistic challenges by validating the authority of the senses, intellect, and testimony, while also providing a coherent mechanism for establishing truth in metaphysical and abstract domains. Ultimately, the article positions al-Taftāzānī’s project as an effective classical Islamic response to epistemic crises of relativism and agnosticism, underscoring its enduring relevance for contemporary philosophical and theological discourse.